2022
DOI: 10.11591/ijpeds.v13.i3.pp1625-1634
|View full text |Cite
|
Sign up to set email alerts
|

Developing a hybrid filter structure and a control algorithm for hybrid power supply

Abstract: The paper presents the results of a study on hybrid filter operation and performance under hybrid power supply. In the study, a hybrid filter structure was developed and proved to perform a set of power quality improving functions. The paper demonstrates that it is necessary for the hybrid filter structure to be variable in order to adapt to changes in power supply. A case is made for using an additional passive filter at the active part output of the hybrid filter under distributed generation. The optimal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The distributed generation aggregation buses in the algorithm are designed in different models depending on the type of distributed generator, its interface connection, and its operation method. They can be classified according to the following categories [9,10].…”
Section: Modeling Of the Distributed Regenerative Generation Assembly...mentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed generation aggregation buses in the algorithm are designed in different models depending on the type of distributed generator, its interface connection, and its operation method. They can be classified according to the following categories [9,10].…”
Section: Modeling Of the Distributed Regenerative Generation Assembly...mentioning
confidence: 99%
“…The Voltage rise index of a collector bus (VRI%) is the ratio of the difference between its voltage in the presence of DG in the distribution network (V + DG) and its voltage without DG (V-DG), to the voltage without DG 𝑉𝑅𝐼% 100 (10) Some codes, such as the German VDEW, do not allow to exceed VRI% = 2%, but this number is suitable for strong networks, that is, those that have a normal voltage profile, but for weak networks, this indicator remains useful only as an indication [16,17]. Over the support of the distributed generation of voltage.…”
Section: Voltage Rise Index (Vri)mentioning
confidence: 99%
“…Within the framework of oil and gas production, due to its specificity of being strictly tied to a certain geographical location, the problem of creating or maintaining and developing already existing infrastructure elements is particularly acute. The Arctic zone of the Russian Federation should be singled out as a separate region, consisting almost entirely of underdeveloped territories of various constituent entities of the Russian Federation, as it is currently of major strategic interest to Russia due to its enormous resource potential [22][23][24].…”
Section: An Overview Of the Characteristics Of Underdeveloped Areas I...mentioning
confidence: 99%
“…Existing approaches to improving efficiency, ensuring optimal dynamic and energy characteristics (Vasilyeva et al, 2021;Savard et al, 2021) as well as maintaining performance are largely based on the scalar control system of the electric drive. Analysis of research has shown the relevance of developing control algorithms for electric drive systems, taking into account the presence of defects in the IM (Sychev et al, 2022;Klyuev et al, 2021). However, the analysis and development of algorithms that take into account the change in stator magnetization inductance in the presence of an inter-turn fault have not been given due attention in the current literature.…”
Section: Induction Motors Deterioration and Defectsmentioning
confidence: 99%